Exploring the relationship between mental health and dialect use among Chinese older adults: a moderated mediation estimation - Li, Tianxin; Li, Jin; Ke, Xigang (Frontiers in Psychology, 2023)
Background: Mental health, conceptualized as psychological status that includes rational cognition, emotional stability, interpersonal harmony, is highly relevant to the expected health and well-being of all humans. China is facing the dual risk of increased aging and mental health disorders in older adults, while the established studies have rarely focused on the influence of dialect on the mental health of Chinese older adults. The present study aims to capture the relationship between dialect and mental health for Chinese older adults. Methods: We use cross-sectional data from the nationally representative China Family Panel Studies, which encompasses dialects use, mental health and other socioeconomic features of 4420 respondents. We construct a moderated mediation model that takes dialects and mental health as the independent and dependent variable, the income inequality and subjective well-being as the mediator and moderator, to reveal the relationship between dialect and mental health of Chinese older adults. Results: (1) Dialects pose negative influence on mental health of older adults in the current study (coefficient = -0.354, 95% CI = [-0.608, -0.097]), (2) Income inequality positively mediates the correlation between dialects and mental health (coefficient = 0.019, 95% CI = [0.010, 0.045]), (3) Subjective well-being negatively moderates the potential mechanism between dialects and mental health (coefficient = -0.126, 95% CI = [-0.284, -0.010]). Conclusions: The use of dialects is associated with worse mental health outcomes in Chinese older adults, while this negative influence is positively mediated by income inequality and negatively moderated by subjective well-being, simultaneously. This study contributes to the knowledge enrichment of government workers, older adults with mental disorders older adults, medical staff and other stakeholders.